The influence of religion and religiosity on food waste generation among restaurant clienteles - Hassan, Hussein F.; Ghandour, Lilian A.; Chalak, Ali; Aoun, Pamela; Reynolds, Christian J.; Abiad, Mohamad G. (Frontiers in Sustainable Food Systems, 2022)
Introduction Food waste is a global issue of primary concern due to its repercussions on the environment, food security, and the economy. Our study aimed to explore the impact of religion and religiosity on food waste generation among restaurant clienteles in Lebanon, a religiously diverse country. Methods A convenient sample of 927 restaurant patrons dining out in Greater Beirut was interviewed face-to-face, and leftovers at each table were collected and weighed. Results Christian diners were found to waste significantly less (p < 0.05) than Druze and Muslim patrons in restaurants serving Lebanese and non-Lebanese food. Individuals (19.1% of respondents) from both religions who reported that their relationship with God is the priority in life waste similarly compared to those who claimed to have other priorities. The higher the religiosity score among both Christians and Muslims/Druze groups was, the lower the food waste quantity got, highlighting the reduced wasteful behavior among highly religious people. Discussion Based on these findings, including religious cues in consumer-based interventions to reduce food waste can be more effective. This can be achieved through marketing campaigns that communicate religious-based messages to trigger religious beliefs that reduce food waste, using physical spaces and rituals of mosques and churches.